Avaliç\~ao de impacto da Lei de Informática utilizando os métodos Propensity Score Matching e diferenças em diferenças - Antonio Sergio Malaquias Queroz De Filho; Bruno César Pino Oliveira De Araújo; Mauro Oddo Nogueira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This article assesses the impact of the Informatics Law on the technological efforts of firms, measured by the hiring of personnel in technical-scientific occupations (PoTec). Using Propensity Score Matching (PSM) combined with differences-in-differences between 2006 and 2017, we cannot conclude that technological efforts beneficiary firms of the Informatics Law are significantly superior to the control group. Secondarily, the Information Technology Law had a positive effect on the market share of total wages within the beneficiary sector. These results are in line with other studies that apply counterfactual techniques, with negligible impacts on technological development and some impact on production, even though directed at assembly activities of lesser technological intensity.
Keywords: O31; O38; 330; Informatics Law; RD&I; PoTec; propensity score matching; diff-in-diff